Physical and Mechanical Properties of Bulk-Fill, Conventional, and Flowable Resin Composites Stored Dry and Wet - Dana Jafarpour; Reihaneh Ferooz; Maryam Ferooz; Rafat Bagheri (International Journal of Dentistry)
Surface degradation, margin, and bulk fracture are common reasons that necessitate replacement of resin composite restorations. The purpose of this study was to determine filler weight (FW), fracture toughness (FT), Vickers hardness (VHN), sorption/solubility (S/S), and colour change (ΔE) of four resin composites in dry and wet conditions. Four resin composites of shade A2 were investigated: Aura bulk-fill (AB) (SDI), Tetric Evoceram (TE) (Ivoclar), G-ænial Universal Flo (GUF) (GC), and GC Kalore (GCK) (GC). For FT, VHN, and ΔE, the specimens were prepared, divided into 2 groups, and stored dry or immersed in distilled water. The specimens were subdivided into three subgroups and stored for 1, 7, and 60 days and then subjected to the relevant tests. Six fractured remnants were weighed for each material to measure FW%. To test S/S, ISO 4049 was used. The data were analysed using ANOVA and Tukey’s test. There was an inverse correlation between FW and FT. A significantly higher FT was found for GUF. There were no significant differences between conditions in materials except for AB. The highest VHN was found for GCK and AB. After 1 and 7 days, a significant difference was observed in S/S between all materials with the highest values for GUF. There was a correlation between sorption and solubility. The material, the media, and aging have an influence on the properties of resin composites. It is important to emphasise that each material should be used for a specific clinical need based on their properties.